Natural products from Malaysian rainforests - Ee, Gwendoline Cheng Lian (Universiti Putra Malaysia Press, 2013)
Plants have played an important role in the ancient culture of India, China and Egypt as medicine. Plants have been and always will be an important source of new drugs and new drug leads. Drug discovery based on plants have resulted in the development of anticancer agents and continues to contribute to new leads in clinical trials. The discovery of Cinchona in the 17th century, followed by Digitalis, morphine and then the introduction of synthetic aspirin, a derivative of a plant-based drug, have led human beings to believe in the many wonders of the wealth of the forests. Natural products have provided challenging synthetic targets and their biological activity has given leads for the development of valuable medicines. Screening programmes exist for bioactive compounds and these have led to new drugs, example: taxol - which is used for the treatment of various cancers. Natural products also play a role in ecology by regulating the interactions between plants, microorganisms, insects, and animals. These can be defensive substances, anti feedants, attractants, and pheromones. Chemotaxonomy is another reason for scientists to study natural products. Chemotaxonomy involves the use of natural products in the classification of species, e.g. alkaloids are typically present in the Annonaceae family especially in Kopsiaspecies, or xanthones are typically present in Garciniaspecies while coumarins are typical of Calophyllumspecies. Phytochemical surveys can also reveal natural products that are markers for botanical and evolutionary relationships. The study of natural products have resulted in modern techniques for separation, structural elucidation, screening and combinatorial synthesis have led to increased interest in plant natural products as sources of new drugs. The introduction of herbal products in the form of nutraceuticals and dietary supplements are also changing the plant-based drug market.